PENGEMBANGAN SISTEM INFORMASI SIMPAN PINJAM PADA KOPERASI WREDATAMA KRAKATAU STEEL (KOPWEKAS) - Khasan Asrori; Darpi Darpi; Sawitri Nurhayati (LPPM Unbaja, 2022)
The main activity of cooperatives is to carry out savings and loan transactions for cooperative members only. Every transaction carried out at the Wredatama Krakatau Steel Cooperative (Kopwekas) already uses a database-based application that only requires a few problems including data collection on deposits, credit data collection, and payment processing as well as arrears of cooperative members. It is necessary to develop a savings and loan information system. The methodology used in the design of this information system is the Waterfall Method. This system is designed using the concepts of UML (Unifield Modeling Language) and implemented using Microsoft SQL Server 2000 Database, and Visual Basic 6.0. The expected result of this research is the development of a savings and loan information system of kopwekas which includes processing of deposits, credit, payments and arrears of cooperative members. By using this information system, it is also hoped that the reporting process will be easier, faster with accurate data. Keywords: Information System, Savings and Loans, Waterfall, Cooperative